PENINGKATAN PEMAHAMAN SAINS TENTANG ENERGI PADA ANAK USIA DINI MELALUI AKTIVITAS EKSPERIMEN SEDERHANA - Misriatun, Sindi (Jurnal Anak Bangsa, 2024)
This study aims to improve the understanding of the concept of energy in early childhood through simple experimental activities at RA Al-Ihya. The research method used is Classroom Action Research (CAR) with a qualitative descriptive approach, which is carried out in four cycles including planning, implementation, observation, and reflection. The experiments carried out include the concepts of heat energy, wind energy, and kinetic energy, designed to suit the cognitive development of early childhood. The results of the study showed that children experienced a significant increase in understanding of the concept of energy after participating in the experiment. In the first cycle, children began to understand that sunlight can change the temperature of objects. The second and third cycles showed that children could relate wind and thrust to the movement of objects. Evaluation in the fourth cycle showed that children were actively involved and used simple scientific language to explain the phenomena they observed. Simple experimental activities have proven effective in increasing children's engagement and enthusiasm for science. Despite challenges such as language limitations and differences in cognitive development, the results of this study suggest that an experiment-based approach can strengthen the understanding of science concepts in early childhood. This study makes an important contribution to science learning methods in early childhood education and emphasizes the role of teachers in supporting active and interactive learning